Bank liquidity risk in participatory banks. Which perspectives for Moroccan market ? - LOTFI , Mohamed; ELAATCHI , Mounia (Revue du contrôle, de la comptabilité et de l’audit, 2022)
When a participatory finance has proven the viability and stability of its model alongside conventional finance in many countries, the problem of managing its liquidity is a major issue in winning new clients. Of course, participatory banks are subject to liquidity risk just as conventional banks are (Sundararajan et Errico 2002); Akkisisdis & Khandelwal, 2008; Al-Muharrami & Hardy, 2013). However, their responsiveness and flexibility to liquidity risk is very limited due to Shariah compliance requirements and the fragility of their financial ecosystem, forcing them to guarantee their solvency on the one hand and to protect themselves against liquidity risk by holding large amounts of cash instead of investing it. This paper will discuss the topic with an overview of risk liquidity in participatory market, then approach and analyse issues and ways to come up with the liquidity constraints in Moroccan financal market.